Alpha7-acetylcholine receptor antibodies in two patients with Rasmussen encephalitis. - Watson, R; Jepson, J; Bermudez, I; Alexander, S; Hart, Y; McKnight, K; Roubertie, A; Fecto, F; Valmier, J; Sattelle, D; Beeson, D; Vincent, A; et al. (2005)
Rasmussen encephalitis (RE) sera were screened for antibodies to human alpha7 nicotinic acetylcholine receptors (nAChRs) using electrophysiology, calcium imaging, and ligand binding assays. Sera from two of nine patients with RE blocked ACh-induced currents through alpha7 nAChRs and the ACh-induced rise in intracellular free calcium ([Ca2+]i) and inhibited (125)I-alpha-bungarotoxin binding in cells expressing alpha7 nAChRs. Thus, the alpha7 nAChR is a potential target for pathogenic antibodies in patients with RE.